Analysis of meniscal hoop strain in porcine knees - Chua, Keith Ing Chong (2017)
Menisci in the human knee joints are two C-shaped cartilages which are predominantly made up of a network of collagen fibres. They play a very pivotal role in the biomechanics of the knee joint with their load bearing ability. As such, meniscal injuries or degeneration could lead to undesired consequences such as arthritis of the knee joint. Injuries to the meniscus are usually treated with methods such as meniscectomy or meniscal repair. However, the effectiveness of the treatments being used may be undermined without a fundamental understanding of the meniscus mechanics. The hoop stress theory suggests that the load across a knee joint are distributed into the circumferential fibres in a meniscus resulting in hoop strains being generated. The objective of this study was to measure the hoop strain that was generated at the peripheral rim of the intact meniscus and with a 50% radial tear at flexion angles of 30°, 45° and 60°. This study serves to quantify the hoop strain values measured in a porcine meniscus and analyse this animal model since porcine knees are commonly used as a substitute for human knees in various studies. From the strain measured, it allows us to better understand meniscus mechanics during the stance phase of the gait cycle. A total of 8 porcine knee joints were used for this study, but only 3 specimens were experimented using a newly designed femoral jig midway into the study. The specimens were mounted onto a custom-designed fixture in an Instron machine and was subjected to a compressive loading of 1400 N. The trend of the results showed that the posterior medial recorded a higher strain than the other regions. The strain recorded in the posterior medial side was also significantly higher (P = 0.026) than that recorded in the posterior lateral and anterior lateral (P = 0.029) of the intact meniscus at 60° flexion. Results seemed to indicate that the strain of the anterior medial was lower than the strain measured in the posterior medial region of the intact meniscus. From this study, it seemed to suggest that there are different hoop strains measured in different regions of the meniscus under an axial load and the strain distribution is affected by meniscal tears.